2019
DOI: 10.1080/10410236.2019.1652389
|View full text |Cite
|
Sign up to set email alerts
|

Drawing the Line between Sick and Healthy: Normality Constructions in Health Communication Contexts

Abstract: In this paper we examine how traditional views of normality are negotiated, indorsed and resisted when talking about children with heart defects. Having as a starting point an ethnographic project that aimed to study knowledge construction when being pregnant or having a child with a heart defect, we focus on argumentation put forward by clinicians and parents in order to understand the forms that normality takes in relation to children's health and illness and the way that it is constructed argumentatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…S EVERAL NURSING and health care studies have revealed how striving for normalcy plays an important role in patients' quality of life and illness experience [1][2][3][4][5] and, further, how traditional views of normalcy are negotiated, endorsed, and resisted when living with chronic disease. 6 Presumably therefore, the terminology and assumptions surrounding "normal" and the terminology by which we refer to it would be apparent throughout health care systems, and in nurses' communication with patients at hospitals, in primary care, and community-based care settings. 7,8 However, normalcy is a powerful and complex idea, and the term can be used intentionally or unintentionally to various effects.…”
mentioning
confidence: 99%
“…S EVERAL NURSING and health care studies have revealed how striving for normalcy plays an important role in patients' quality of life and illness experience [1][2][3][4][5] and, further, how traditional views of normalcy are negotiated, endorsed, and resisted when living with chronic disease. 6 Presumably therefore, the terminology and assumptions surrounding "normal" and the terminology by which we refer to it would be apparent throughout health care systems, and in nurses' communication with patients at hospitals, in primary care, and community-based care settings. 7,8 However, normalcy is a powerful and complex idea, and the term can be used intentionally or unintentionally to various effects.…”
mentioning
confidence: 99%